Peningkatan Kemampuan Mahasiswa Memecahkan Masalah Melalui Penerapan Pembelajaran Berbasis Proyek Case Method - Adila Solida; Rumita Ena Sari; Rizalia Wardiah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The ability to analyze ethical and health law issues is one of the learning outcomes that must be mastered by students of the Public Health Study Program. Over the past two years, the implementation of lectures has been predominantly based on problem-based learning; however, most student learning outcomes have remained in the “not yet achieved” category, including in completing assignments related to ethical and health law problem solving. This study aims to compare students’ problem-solving abilities between the implementation of project-based learning and problem-based learning. The research was conducted in the Public Health Study Program at Universitas Jambi involving first-semester students enrolled in the Ethics and Health Law course. The research employed a quasi-experimental design involving 200 students, with 100 students assigned to the experimental group and 100 students to the control group. The instruments used were assessment sheets and observation sheets. Data collection was carried out twice, before and after the implementation of the two learning models. Data processing and analysis were conducted using an independent t-test.The results of the study indicate an improvement in students’ problem-solving abilities through the implementation of project-based learning. Project-based learning contributes to strengthening students’ perseverance and problem-solving skills and is therefore recommended for implementation in all courses at higher education institutions.